Adhesive layer, laminate, optical laminate, method for producing optical laminate, and optical device
By controlling the creep deformation rate and introducing a specific polymer in the adhesive layer, combined with the curing of the active energy ray curable resin, the problem of time changes in the adhesive layer invading the recesses of the optical sheet is solved, and the optical laminated body is realized Functional stability and feasibility of mass production.
Patent Information
- Application Number
- CN202180015744.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-02-21
- Filing Date
- 2021-02-19
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2041-02-19
AI Technical Summary
When using an adhesive layer to adhere an optical sheet with an uneven structure on the surface of the adhesive layer, the extent to which the adhesive layer intrudes into the concave portion of the uneven structure will affect the function of the optical sheet. In view of mass production perspective, it is preferable to roll by rolling when manufacturing an optical laminated body when manufacturing a roll-to-roll The method is carried out, and the degree of invasion of the adhesive layer is required to not change over time.
In the creep test of the adhesive layer, a stress of 10000 Pa at 50°C was applied, and the creep deformation rate of the adhesive layer was controlled to be less than 10%, and a polymer such as nitrogen-containing ( Meth)acrylic monomer, carboxyacrylic monomer or polyester polymer are formed by curing the active energy ray curable resin to form an adhesive layer having a crosslinked structure.
The change in time of the degree of the adhesive layer intruding into the recessed portion of the optical sheet is effectively suppressed, and the functional stability of the optical sheet is ensured, and the optical laminate is manufactured by roll-to-roll method, which improves the production efficiency and product consistency.
Smart Images

Figure CN115135738B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an adhesive layer, a laminate having an adhesive layer, a laminate having an adhesive composition layer for forming an adhesive layer, an optical laminate having an adhesive layer and an optical sheet, a method for producing an optical laminate, and an optical device having such an optical laminate. Background Art
[0002] Optical sheets (for example, microlens sheets, prism sheets, brightness enhancement films (for example, Brightness Enhancement Film: BEF (registered trademark) manufactured by 3M)) are used in various optical devices (for example, display devices and lighting devices). In the present specification, "optical sheet" is not limited to the examples exemplified above, but also widely includes sheet-like optical components, such as diffusers and light guide plates. Optical sheets are affixed to other optical sheets or optical devices using, for example, an adhesive layer. In the present specification, "optical laminate" refers to a structure including an optical sheet and an adhesive layer or a structure including a plurality of optical sheets. In the present specification, "adhesive" is used in the sense of including adhesives (also called "pressure-sensitive adhesives").
[0003] The applicant disclosed in Patent Document 1 an optical laminate (referred to as an "optical laminate sheet" in Patent Document 1) that can be used for display devices and lighting devices. The optical laminate of Patent Document 1 comprises: an optical sheet (e.g., a microlens sheet) having a concave-convex structure on its surface, and an adhesive layer disposed on the surface having the concave-convex structure, wherein 5% to 90% of the height of the convex portion of the concave-convex structure is embedded in the adhesive layer, and the adhesive layer is formed by an adhesive composition comprising a graft polymer and a photocationic polymerization initiator or a thermal curing catalyst, wherein the graft polymer is formed by grafting a chain comprising a cyclic ether group-containing monomer with a (meth) acrylic polymer.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2012-007046 (Japanese Patent Publication No. 5658490)
[0007] Patent Document 2: International Publication No. 2019 / 087118 Summary of the invention
[0008] Problem that the invention aims to solve
[0009] When an optical sheet having a concavo-convex structure on its surface is attached using an adhesive layer, the extent to which the adhesive layer intrudes into (fills in) the concave portions of the concavo-convex structure affects the function of the optical sheet. Therefore, it is preferred that the extent to which the adhesive layer intrudes into the concave portions of the concavo-convex structure does not change over time.
[0010] In addition, from the viewpoint of mass productivity, an optical laminate formed by laminating an optical sheet and an adhesive layer or an optical laminate formed by laminating a plurality of optical sheets for use in an optical device can be preferably produced by a roll-to-roll method.
[0011] The present invention is made to solve at least one of the above problems, and its purpose is to provide an adhesive layer in which the degree of the concave part of the concavo-convex structure of the optical sheet is suppressed from changing over time, a laminate having such an adhesive layer, a laminate having an adhesive composition layer capable of forming such an adhesive layer, an optical laminate having such an adhesive layer and an optical sheet, or an optical laminate that can be manufactured by a roll-to-roll method, and a method for manufacturing such an optical laminate. In addition, the present invention aims to provide an optical device having such an optical laminate.
[0012] Solutions to the problem
[0013] According to an embodiment of the present invention, the solution methods described in the following items are provided.
[0014] [Project 1]
[0015] An adhesive layer having a creep deformation rate of 10% or less when a stress of 10,000 Pa is applied at 50° C. for 1 second, and a creep deformation rate of 16% or less when a stress of 10,000 Pa is applied at 50° C. for 30 minutes in a creep test using a rotational rheometer,
[0016] The adhesive layer has a 180° peeling strength with respect to the PMMA film of 10 mN / 20 mm or more.
[0017] [Project 2]
[0018] The adhesive layer according to item 1, wherein the haze is 0.01% to 5%.
[0019] [Item 3]
[0020] The adhesive layer according to item 1 or 2, wherein the thickness is 0.1 μm or more and 20 μm or less.
[0021] The thickness of the adhesive layer is preferably 15 μm or less or 10 μm or less.
[0022] [Item 4]
[0023] The adhesive layer according to any one of items 1 to 3, comprising at least one of the following polymers (1) to (3):
[0024] (1) a copolymer of a nitrogen-containing (meth)acrylic monomer and at least one other monomer;
[0025] (2) a copolymer of a carboxyl group-containing acrylic monomer and at least one other monomer (except a nitrogen-containing (meth) acrylic monomer);
[0026] (3) Polyester polymers.
[0027] [Item 5]
[0028] The adhesive layer according to any one of items 1 to 4, comprising a polyester-based polymer.
[0029] [Item 6]
[0030] The adhesive layer according to any one of items 1 to 5, comprising a (meth)acrylic polymer,
[0031] The (meth)acrylic polymer is a copolymer of a nitrogen-containing (meth)acrylic monomer and at least one other monomer.
[0032] [Item 7]
[0033] The adhesive layer according to item 6, wherein
[0034] The nitrogen-containing (meth)acrylic monomer has a nitrogen-containing cyclic structure.
[0035] [Item 8]
[0036] The adhesive layer according to item 6 or 7, wherein
[0037] The (meth)acrylic polymer is cross-linked.
[0038] [Item 9]
[0039] The adhesive layer according to any one of items 6 to 8, which does not contain a graft polymer.
[0040] [Item 10]
[0041] The adhesive layer according to any one of items 6 to 9, further comprising a cured product of an active energy ray-curable resin.
[0042] [Item 11]
[0043] The adhesive layer according to item 10 is formed by curing the active energy ray-curable resin of the adhesive composition layer containing the (meth)acrylic polymer, the active energy ray-curable resin and a polymerization initiator.
[0044] [Item 12]
[0045] A laminated body comprising:
[0046] The adhesive layer according to any one of items 1 to 10, and
[0047] A substrate having a main surface subjected to a release treatment,
[0048] The release-treated main surface of the substrate is bonded to the adhesive layer.
[0049] The laminated body described in Item 12 may be referred to as an "adhesive sheet".
[0050] The laminated body described in Item 12 may further include another substrate, which is disposed on the opposite side of the adhesive layer from the substrate and has a main surface subjected to a release treatment. In this case, the main surface of the other substrate subjected to the release treatment is bonded to the adhesive.
[0051] The surface that has been subjected to the release treatment (release treatment surface) is referred to as the surface that has been treated with a release agent. The main surface of the substrate (support) that has been subjected to the release treatment is formed by coating (giving) a release agent on one main surface of the substrate and further drying it as needed. The release agent is not particularly limited, and examples thereof include: silicone release agents, fluorine release agents, long-chain alkyl release agents, and fatty amide release agents.
[0052] [Item 13]
[0053] A laminated body comprising:
[0054] The above-mentioned adhesive composition layer forming the adhesive layer according to item 11, and
[0055] A substrate having a main surface subjected to a release treatment,
[0056] The release-treated main surface of the substrate and the adhesive composition layer are bonded together.
[0057] The laminated body described in Item 13 may be referred to as an "adhesive sheet".
[0058] The laminate described in Item 13 may further include another substrate, which is disposed on the opposite side of the adhesive composition layer from the substrate and has a main surface that has been subjected to a release treatment. In this case, the main surface of the other substrate that has been subjected to a release treatment is bonded to the adhesive composition layer.
[0059] [Item 14]
[0060] An optical laminate having:
[0061] A first optical sheet having a first main surface having a concavo-convex structure and a second main surface opposite to the first main surface; and
[0062] The adhesive layer according to any one of items 1 to 11 is disposed on the first main surface side of the first optical sheet.
[0063] [Item 15]
[0064] The optical layered body according to item 14, wherein
[0065] The concavo-convex structure includes a plurality of concave portions, and a plurality of spaces are defined in the plurality of concave portions by the surface of the adhesive layer and the first main surface of the first optical sheet.
[0066] [Item 16]
[0067] The optical layered body according to item 15, wherein
[0068] The concavo-convex structure includes a flat portion in contact with the adhesive layer.
[0069] [Item 17]
[0070] A manufacturing method, which is a method for manufacturing the optical layered body according to any one of items 14 to 16, comprising:
[0071] A step of bonding the first optical sheet and the adhesive layer together.
[0072] [Item 18]
[0073] The manufacturing method according to item 17, wherein:
[0074] The above process is performed by a roll-to-roll method.
[0075] [Item 19]
[0076] The optical layered body according to any one of Items 14 to 16, further comprising a second optical sheet, wherein the second optical sheet is disposed on the side of the adhesive layer opposite to the first optical sheet side.
[0077] [Item 20]
[0078] A production method, which is the production method of the optical layered body according to item 19, comprising any one of step A1 and step A2,
[0079] The step A1 is to bond the first laminate to the second optical sheet, wherein the first laminate is formed by laminating the first optical sheet and the adhesive layer.
[0080] The step A2 is to bond the second laminate to the first optical sheet. The second laminate is formed by laminating the adhesive layer and the second optical sheet.
[0081] [Item 21]
[0082] The manufacturing method according to item 20 comprises:
[0083] The method comprises the step A1, wherein the step A1 comprises a step of bonding the first laminate and the second optical sheet by a roll-to-roll method; or
[0084] This method includes the step A2, and the step A2 includes a step of bonding the second laminate and the first optical sheet together by a roll-to-roll method.
[0085] [Item 22]
[0086] An optical device comprising the optical layered body according to any one of items 14 to 16 and 19.
[0087] [Item 23]
[0088] A method for producing an optical layered body according to any one of items 14 to 16 directly or indirectly referring to item 11, the method comprising:
[0089] Step A, providing the adhesive composition layer on the first main surface of the first optical sheet; and
[0090] In step B, in a state where the adhesive composition layer is provided on the first main surface of the first optical sheet, the active energy ray-curable resin of the adhesive composition layer is cured.
[0091] [Item 24]
[0092] The manufacturing method according to item 23, wherein:
[0093] The step A includes a step of bonding the first optical sheet and the adhesive composition layer together by a roll-to-roll method.
[0094] [Item 25]
[0095] A manufacturing method, which is the manufacturing method of the optical laminated body described in item 19 indirectly referring to item 11, the method comprising:
[0096] Either step A1 or step A2, and
[0097] In step B after step A1 or step A2,
[0098] The step A1 is to bond the first laminate to the second optical sheet, wherein the first laminate is formed by laminating the first optical sheet and the adhesive composition layer.
[0099] The step A2 is to bond the second laminate to the first optical sheet, wherein the second laminate is formed by laminating the adhesive composition layer and the second optical sheet.
[0100] The step B cures the active energy ray-curable resin contained in the adhesive composition layer.
[0101] [Item 26]
[0102] The manufacturing method according to item 25, wherein:
[0103] The method comprises the step A1, wherein the step A1 includes a step of bonding the first laminate and the second optical sheet by a roll-to-roll method; or
[0104] This method includes the step A2, and the step A2 includes a step of bonding the second laminate and the first optical sheet by a roll-to-roll method.
[0105] Effects of the Invention
[0106] According to an embodiment of the present invention, there are provided an adhesive layer in which the degree of time-dependent change of the concave portion of the concave-convex structure of the optical sheet that is invaded (buried) is suppressed, a laminate having such an adhesive layer, a laminate having an adhesive composition layer capable of forming such an adhesive layer, an optical laminate having such an adhesive layer and an optical sheet, or an optical laminate that can be manufactured by a roll-to-roll method, and a method for manufacturing such an optical laminate. According to another embodiment of the present invention, there is provided an optical device having such an optical laminate. BRIEF DESCRIPTION OF THE DRAWINGS
[0107] Figure 1 It is a schematic cross-sectional view of an optical layered body 100A according to an embodiment of the present invention.
[0108] Figure 2 This is a schematic cross-sectional view of an optical layered body 101A according to another embodiment of the present invention.
[0109] Figure 3 Schematic diagram showing a creep curve of an adhesive.
[0110] Figure 4 It is a schematic cross-sectional view of an optical layered body 100B and an optical layered body 101B according to still another embodiment of the present invention.
[0111] Figure 5 It is a schematic perspective view of the first optical sheet 10 b included in the optical layered body 100B.
[0112] Figure 6 It is a schematic cross-sectional view of a lighting device 200 including an optical layered body 100B.
[0113] Fig. 7A It is a schematic plan view of a shaped film 70 included in the optical layered body according to the embodiment of the present invention.
[0114] Figure 7B 70 is a schematic cross-sectional view of the excipient film 70 .
[0115] Explanation of symbols
[0116] 10a, 10b First optical sheet
[0117] 12s, 18s main surface (surface)
[0118] 20a, 20b Adhesive layer
[0119] 30 2nd optical sheet
[0120] 32s, 38s main surface (surface)
[0121] 50 Light guide plate
[0122] 60 Light Source
[0123] 100A, 100B, 101A, 101B, 102B Optical laminate
[0124] 200 lighting fixtures DETAILED DESCRIPTION
[0125] First, an adhesive layer according to an embodiment of the present invention, a laminate having an adhesive layer, a laminate having an adhesive composition layer for forming an adhesive layer, an optical laminate having an adhesive layer and an optical sheet, and a method for producing an optical laminate are described.
[0126] Figure 1 and Figure 2 Schematic cross-sectional views of optical layered bodies 100A and 101A according to embodiments of the present invention are shown in FIG. Figure 1 As shown, the optical laminate 100A has an adhesive layer 20a on the concavo-convex structure of the prism surface (first main surface) 12s of the prism sheet (first optical sheet) 10a. Other optical sheets (such as microlens sheets) may be used instead of the prism sheet 10a. Figure 2 As shown, the optical laminate 101A includes the optical laminate 100A and the second optical sheet 30 disposed on the side of the adhesive layer 20a opposite to the first optical sheet 10a. Unless otherwise specified, the description of the optical laminate 100A also applies to the optical laminate 101A, so the description may be omitted to avoid duplication.
[0127] In the manufacturing process of the optical laminate 100A (or the optical laminate 101A), it is required that when the adhesive layer 20a is attached to the prism sheet 10a by, for example, a roll-to-roll method, the adhesive layer 20a does not excessively intrude into the concave portion of the concave-convex structure of the prism sheet 10a. In addition, it is required that after the adhesive layer 20a is attached to the prism sheet 10a, the degree to which the adhesive layer 20a intrudes into the concave portion is not easily changed over time.
[0128] The present inventors have found that there is a correlation between the creep deformation rate of the adhesive layer 20a and the penetration degree of the adhesive layer 20a when attached to the prism sheet 10a and the change in the penetration degree over time, and that the creep deformation rate can be used to select an appropriate adhesive layer.
[0129] Generally speaking, when a constant stress acts on a viscoelastic polymer, such as Figure 3 As shown in the creep curve, the phenomenon (creep) of strain (deformation rate) increasing with time occurs. The strain of a viscoelastic body when a constant stress is applied includes: an elastic component generated instantly when the stress is applied, a viscoelastic component expressed as a function of time and reaching a constant value after a long time, and a viscous component that increases in proportion to time. Due to the viscous component, the strain continues to increase at a certain rate after a long time. After the stress is removed, the viscous component of the strain remains and does not recover.
[0130] The degree to which the adhesive layer 20a intrudes into the recess when the adhesive layer 20a is bonded is related to the creep strain (referred to as "creep deformation rate A") of the adhesive layer 20a after 1 second. That is, the degree to which the adhesive layer 20a intrudes into the recess when the adhesive layer 20a is bonded is mainly affected by the elastic component of the adhesive layer 20a. On the other hand, the time-dependent change in the degree to which the adhesive layer 20a intrudes into the recess is related to the creep strain (referred to as "creep deformation rate B") of the adhesive layer 20a after 30 minutes (1800 seconds). That is, the time-dependent change in the degree to which the adhesive layer 20a intrudes into the recess is mainly affected by the viscoelastic component and the viscous component of the adhesive layer 20a. It should be noted that the degree to which the adhesive layer 20a intrudes into the recess can be evaluated by the diffuse transmittance of the optical laminate 100A. The greater the degree to which the adhesive layer 20a intrudes into the recess of the prism sheet 10a, the smaller the diffuse transmittance. Creep deformation includes a stage at the beginning of deformation called transient creep (first creep) where the strain rate (slope of the creep curve) gradually decreases, and a stage called stable creep (second creep) where the strain rate becomes almost constant. Figure 3 As shown, 30 minutes (1800 seconds) after the pressure is applied is the time point belonging to the stable creep region after the transient creep.
[0131] As described in the experimental examples below, the adhesive layer 20a of the optical laminate 100A according to the embodiment of the present invention has a creep deformation rate A of 10% or less when a stress of 10,000 Pa is applied for 1 second at 50°C in a creep test using a rotational rheometer, and a creep deformation rate B of 16% or less when a stress of 10,000 Pa is applied for 30 minutes at 50°C in a creep test using a rotational rheometer. The experimental examples also show the evaluation results of the diffuse transmittance of the optical laminate. It should be noted that the creep deformation rates A and B of the adhesive layer and the diffuse transmittance of the optical laminate can be measured, for example, by the method described in the experimental examples described below.
[0132] The adhesive layer 20a having a creep deformation rate A of 10% or less suppresses the degree of invasion of the adhesive layer 20a into the recessed portion to a sufficiently small level during lamination. The adhesive layer 20a having a creep deformation rate B of 16% or less sufficiently suppresses the time-dependent change in the degree of invasion into the recessed portion. The creep deformation rate A of the adhesive layer 20a is, for example, 10% or less, 9% or less, 8% or less, 7% or less, 6% or less, or 5% or less, and the creep deformation rate B of the adhesive layer 20a is, for example, 16% or less, 15% or less, 14% or less, 13% or less, 12% or less, 11% or less, or 10% or less. The lower limits of the creep deformation rates A and B are not particularly limited, and are, for example, greater than 0. It is more preferred that the creep deformation rate A of the adhesive layer 20a is 8% or less and the creep deformation rate B is 14% or less, and it is further preferred that the creep deformation rate A is 5% or less and the creep deformation rate B is 10% or less.
[0133] The second optical sheet 30 has a principal surface 38s on the side of the adhesive layer 20a and a principal surface 32s on the opposite side of the principal surface 38s, and the principal surface 38s is a flat surface. The second optical sheet 30 can be made of any appropriate material according to the purpose. As the material of the second optical sheet 30, for example, it can be mentioned: a thermoplastic resin with light transmittance, more specifically, for example, it can be mentioned: a film formed by (methyl) acrylic resins such as polymethyl methacrylate (PMMA) or polycarbonate (PC) resins. At least one other optical component (or optical sheet) can be configured on the opposite side of the adhesive layer 20a (i.e., on the principal surface 32s) of the second optical sheet 30 of the optical laminate 101A. Other optical components (optical sheets) include, for example, a diffuser, a light guide plate, etc., which are bonded to the principal surface 32s of the optical sheet 30 through an adhesive layer. That is, the optical stack according to another embodiment of the present invention includes an optical stack 101A and at least one other optical sheet disposed on the side opposite to the adhesive layer 20a of the second optical sheet 30 of the optical stack 101A. The optical device according to another embodiment of the present invention includes an optical stack 101A and other optical components disposed on the side opposite to the adhesive layer 20a of the second optical sheet 30 of the optical stack 101A.
[0134] The 180° peeling adhesion of the adhesive layer 20a relative to the PMMA film is, for example, 10mN / 20mm or more. The upper limit is not particularly limited, for example, 50N / 20mm or less, 40N / 20mm or less, 30N / 20mm or less, 20N / 20mm or less, 10N / 20mm or less, or 1N / 20mm or less. The haze of the adhesive layer 20a is, for example, 0.01% or more, and 5% or less, 4% or less, 3% or less, 2% or less, or 1.5% or less. The thickness of the adhesive layer 20a is, for example, 0.1μm or more, 0.5μm or more, or 1.0μm or more, and 20μm or less, 15μm or less, 10μm or less, or 5μm or less. The adhesive layer 20a is used to adhere the optical laminate 100A to other optical sheets or optical devices. In addition, the 180° peeling adhesive strength of the adhesive layer with respect to the PMMA film and the haze of the adhesive layer can be measured by the method described in the experimental examples described later, for example.
[0135] As the adhesive forming the adhesive layer 20 a , the following adhesives can be appropriately used as described later with reference to experimental examples.
[0136] The adhesive contains, for example, a (meth)acrylic polymer, which is, for example, a copolymer of a nitrogen-containing (meth)acrylic monomer and at least one other monomer. The nitrogen-containing (meth)acrylic monomer has, for example, a nitrogen-containing cyclic structure. If the (meth)acrylic polymer is prepared using a nitrogen-containing (meth)acrylic monomer, particularly when the nitrogen-containing (meth)acrylic monomer has a nitrogen-containing cyclic structure, the elastic properties of the (meth)acrylic polymer can be improved.
[0137] In the case where the adhesive contains a (meth) acrylic polymer, the (meth) acrylic polymer is preferably cross-linked. In addition, in the case where the adhesive contains a (meth) acrylic polymer, the adhesive may further include an active energy ray curable resin (e.g., an ultraviolet curable resin) and a curing agent (e.g., a photopolymerization initiator), or may further include a cured product of an active energy ray curable resin. Active energy rays are, for example, visible light and ultraviolet rays. By introducing a cross-linked structure into the adhesive, deformation and time-dependent deformation during pasting of the adhesive can be suppressed. In particular, by curing the active energy ray curable resin after imparting an adhesive composition layer (forming an adhesive layer 20a) to the optical sheet 10a, the time-dependent change of the adhesive layer 20a can be suppressed, thereby suppressing the time-dependent change of the degree of the adhesive layer 20a intruding into the recess. It should be noted that if the active energy ray curable resin is cured, the adhesive layer 20a becomes hard. If the adhesive layer 20a is too hard, it may be difficult to bond the adhesive layer 20a to the optical sheet 10a by a roll-to-roll method. However, this problem can be avoided by curing the active energy ray-curable resin after providing the adhesive composition layer on the optical sheet 10a.
[0138] The adhesive layer 20a containing the cured product of the active energy ray curable resin is formed, for example, by the following method. First, an adhesive composition solution layer is formed by an adhesive composition solution containing a (meth) acrylic polymer, a crosslinking agent, an active energy ray curable resin, a polymerization initiator and a solvent. The adhesive composition solution layer is formed, for example, on the main surface of the substrate that has been subjected to a peeling treatment. Next, the solvent of the adhesive composition solution layer is removed, and the (meth) acrylic polymer of the adhesive composition solution layer is crosslinked using a crosslinking agent (for example, by heating), thereby obtaining an adhesive composition layer having a crosslinked structure. In the case where the adhesive composition solution layer is formed on the main surface of the substrate that has been subjected to a peeling treatment, an adhesive composition layer is formed on the main surface of the substrate that has been subjected to a peeling treatment, and a laminate having a substrate and an adhesive composition layer is obtained. Here, the crosslinked structure formed by the (meth) acrylic polymer and the crosslinking agent is referred to as the first crosslinked structure, which is distinguished from the crosslinked structure (the second crosslinked structure) formed by curing the active energy ray curable resin described later. The polymer of the adhesive composition solution layer can be cross-linked in the process of removing the solvent of the adhesive composition solution layer, or the process of cross-linking the polymer of the adhesive composition solution layer can be further performed in a manner separate from the process of removing the solvent of the adhesive composition solution layer after the process of removing the solvent of the adhesive composition solution layer. Then, the adhesive composition layer is attached to the first main surface 12s of the optical sheet 10a, and the adhesive composition layer is irradiated with active energy rays in a state where the adhesive composition layer is arranged on the first main surface 12s of the optical sheet 10a, so that the active energy ray curable resin is cured, thereby forming an adhesive layer 20a having a second cross-linked structure in addition to the first cross-linked structure. It is believed that the first cross-linked structure and the second cross-linked structure possessed by the adhesive layer 20a form a so-called interpenetrating network structure (IPN).
[0139] The adhesive layer 20a containing no cured product of active energy ray-curable resin is formed, for example, by the following method. First, an adhesive composition solution layer is formed from an adhesive composition solution containing a polymer, a crosslinking agent and a solvent. The adhesive composition solution does not contain an active energy ray-curable resin and a polymerization initiator. The adhesive composition solution layer is formed, for example, on the main surface of the substrate that has been subjected to a peeling treatment. Next, the solvent of the adhesive composition solution layer is removed, and the polymer of the adhesive composition solution layer is crosslinked using a crosslinking agent (for example, by heating), thereby obtaining an adhesive layer 20a having a crosslinked structure. In the case where the adhesive composition solution layer is formed on the main surface of the substrate that has been subjected to a peeling treatment, an adhesive layer is formed on the main surface of the substrate that has been subjected to a peeling treatment, and a laminate having a substrate and an adhesive layer is obtained. The polymer of the adhesive composition solution layer can be crosslinked in the process of removing the solvent of the adhesive composition solution layer, or after the process of removing the solvent of the adhesive composition solution layer, a process of crosslinking the polymer of the adhesive composition solution layer can be further performed in a manner separate from the process of removing the solvent of the adhesive composition solution layer.
[0140] The adhesive preferably does not contain a graft polymer. If the adhesive layer described in Patent Document 1 is formed from an adhesive composition containing a graft polymer, the design factors and control factors of the material become more numerous, and mass production is sometimes poor. The creep properties of the adhesive not containing a graft polymer can be adjusted according to various factors (e.g., the type and amount of the crosslinking agent, the type and amount of the active energy ray-curable resin).
[0141] Preferred specific examples of the adhesive are described below.
[0142] The adhesive includes, for example, a (meth)acrylic polymer. As a monomer for producing the (meth)acrylic polymer, any (meth)acrylic ester can be used without particular limitation. For example, an alkyl (meth)acrylate having an alkyl group with 4 or more carbon atoms can be used. In this case, the proportion of the alkyl (meth)acrylate having an alkyl group with 4 or more carbon atoms relative to the total amount of the monomer for producing the (meth)acrylic polymer is, for example, 50% by mass or more.
[0143] In this specification, "alkyl (meth)acrylate" refers to a (meth)acrylate having a linear or branched alkyl group. The carbon number of the alkyl group in the alkyl (meth)acrylate is preferably 4 or more, more preferably 4 or more and 9 or less. It should be noted that (meth)acrylate refers to acrylate and / or methacrylate.
[0144] Specific examples of the alkyl (meth)acrylate include n-butyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, isopentyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, n-dodecyl (meth)acrylate, isotetradecyl (meth)acrylate, n-tridecyl (meth)acrylate, n-tetradecyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, etc. These alkyl (meth)acrylates may be used alone or in combination.
[0145] The adhesive may include a (meth)acrylic polymer which is a copolymer of a nitrogen-containing (meth)acrylic monomer and at least one other monomer. In this case, the (meth)acrylic polymer is preferably a copolymer obtained by copolymerizing the following monomers in the following amounts when the total amount of the monomers used for copolymerization is 100 parts by mass.
[0146] Nitrogen-containing (meth)acrylic monomer: 10.0 parts by mass or more, 15.0 parts by mass or more, 20.0 parts by mass or more, 25.0 parts by mass or more, 30.0 parts by mass or more, or 35.0 parts by mass or more, and 40.0 parts by mass or less, 35.0 parts by mass or less, 30.0 parts by mass or less, 25.0 parts by mass or less, 20.0 parts by mass or less, or 15.0 parts by mass or less. For example, 10.0 parts by mass or more and 40.0 parts by mass or less.
[0147] Hydroxyl-containing acrylic monomer: 0.05 parts by mass or more, 0.75 parts by mass or more, 1.0 parts by mass or more, 2.0 parts by mass or more, 3.0 parts by mass or more, 4.0 parts by mass or more, 5.0 parts by mass or more, 6.0 parts by mass or more, 7.0 parts by mass or more, 8.0 parts by mass or more, or 9.0 parts by mass or more, and 10.0 parts by mass or less, 9.0 parts by mass or less, 8.0 parts by mass or less, 7.0 parts by mass or less, 6.0 parts by mass or less, 5.0 parts by mass or less, 4.0 parts by mass or less, 3.0 parts by mass or less, 2.0 parts by mass or less, or 1.0 parts by mass or less. For example, 0.05 parts by mass or more and 10.0 parts by mass or less.
[0148] Carboxyl group-containing acrylic monomer: 1.0 mass parts or more, 2.0 mass parts or more, 3.0 mass parts or more, 4.0 mass parts or more, 5.0 mass parts or more, 6.0 mass parts or more, 7.0 mass parts or more, 8.0 mass parts or more, or 9.0 mass parts or more, and 10.0 mass parts or less, 9.0 mass parts or less, 8.0 mass parts or less, 7.0 mass parts or less, 6.0 mass parts or less, 5.0 mass parts or less, 4.0 mass parts or less, 3.0 mass parts or less, or 2.0 mass parts or less. For example, 1.0 mass parts or more and 10.0 mass parts or less.
[0149] (Meth) alkyl acrylate monomer: (100 parts by mass) - (total amount of monomers other than the (meth) alkyl acrylate monomer used for copolymerization)
[0150] In this specification, "nitrogen-containing (meth) acrylic monomers" include, without particular limitation, monomers having a polymerizable functional group having an unsaturated double bond such as a (meth) acryloyl group and having a nitrogen atom. "Nitrogen-containing (meth) acrylic monomers" have, for example, a nitrogen-containing cyclic structure. Examples of nitrogen-containing (meth) acrylic monomers having a nitrogen-containing cyclic structure include: N-vinyl-2-pyrrolidone (NVP), N-vinyl-ε-caprolactam (NVC), and 4-acryloylmorpholine (ACMO). These nitrogen-containing cyclic structures can be used alone or in combination.
[0151] In the present specification, "hydroxyl-containing acrylic monomers" include, without particular limitation, monomers having a polymerizable functional group having an unsaturated double bond such as a (meth)acryloyl group and having a hydroxyl group. Examples thereof include: hydroxyalkyl (meth)acrylates such as 2-hydroxybutyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxylauryl (meth)acrylate; 4-hydroxymethylcyclohexyl (meth)acrylate, 4-hydroxybutyl vinyl ether, and the like.
[0152] In this specification, "carboxyl group-containing acrylic monomers" include, without particular limitation, monomers having a polymerizable functional group having an unsaturated double bond such as a (meth)acryloyl group or a vinyl group and having a carboxyl group. Examples of unsaturated carboxylic acid-containing monomers include (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, and the like. These unsaturated carboxylic acid-containing monomers may be used alone or in combination.
[0153] The adhesive may contain a (meth) acrylic polymer, which is a copolymer of a carboxyl group-containing acrylic monomer and at least one other monomer (excluding the nitrogen-containing (meth) acrylic monomer). In this case, the (meth) acrylic polymer is preferably a copolymer obtained by copolymerizing the following monomers in the following amounts when the total amount of the monomers used for copolymerization is 100 parts by mass.
[0154] Carboxyl group-containing acrylic monomer: 1.0 mass parts or more, 2.0 mass parts or more, 3.0 mass parts or more, 4.0 mass parts or more, 5.0 mass parts or more, 6.0 mass parts or more, 7.0 mass parts or more, 8.0 mass parts or more, or 9.0 mass parts or more, and 10.0 mass parts or less, 9.0 mass parts or less, 8.0 mass parts or less, 7.0 mass parts or less, 6.0 mass parts or less, 5.0 mass parts or less, 4.0 mass parts or less, 3.0 mass parts or less, or 2.0 mass parts or less. For example, 1.0 mass parts or more and 10.0 mass parts or less.
[0155] (Meth) alkyl acrylate monomer: 90.0 parts by mass or more, 91.0 parts by mass or more, 92.0 parts by mass or more, 93.0 parts by mass or more, 94.0 parts by mass or more, 95.0 parts by mass or more, 96.0 parts by mass or more, 97.0 parts by mass or more, or 98.0 parts by mass or more, and 99.0 parts by mass or less, 98.0 parts by mass or less, 97.0 parts by mass or less, 96.0 parts by mass or less, 95.0 parts by mass or less, 94.0 parts by mass or less, 93.0 parts by mass or less, 92.0 parts by mass or less, or 91.0 parts by mass or less. For example, 90.0 parts by mass or more and 99.0 parts by mass or less.
[0156] Examples of crosslinking agents for introducing a crosslinked structure into a (meth)acrylic polymer include isocyanate crosslinking agents, epoxy crosslinking agents, silicone crosslinking agents, Crosslinking agents such as oxazoline crosslinking agents, aziridine crosslinking agents, silane crosslinking agents, alkyl etherified melamine crosslinking agents, metal chelate crosslinking agents, and peroxides. The crosslinking agents may be used alone or in combination of two or more.
[0157] The isocyanate crosslinking agent refers to a compound having two isocyanate groups (including isocyanate regenerating functional groups in which the isocyanate groups are temporarily protected by a blocking agent or polymerization) in one molecule.
[0158] Examples of the isocyanate crosslinking agent include aromatic isocyanates such as tolylene diisocyanate and xylene diisocyanate, alicyclic isocyanates such as isophorone diisocyanate, and aliphatic isocyanates such as hexamethylene diisocyanate.
[0159] More specifically, for example, lower aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate, alicyclic isocyanates such as cyclopentene diisocyanate, cyclohexene diisocyanate and isophorone diisocyanate, aromatic diisocyanates such as 2,4-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, xylylene diisocyanate and polymethylene polyphenyl isocyanate, trimethylolpropane / toluene diisocyanate trimer adduct (manufactured by Tosoh Corporation, trade name Coronate L), trimethylolpropane / hexamethylene diisocyanate trimer adduct (manufactured by Tosoh Corporation, trade name Coronate HL), isocyanurate of hexamethylene diisocyanate (manufactured by Tosoh Corporation, trade name Coronate isocyanate adducts such as trimethylolpropane adduct of xylylene diisocyanate (Mitsui Chemicals, Inc., trade name D110N), trimethylolpropane adduct of hexamethylene diisocyanate (Mitsui Chemicals, Inc., trade name D160N); polyether polyisocyanates, polyester polyisocyanates, and adducts thereof with various polyols, polyisocyanates obtained by multifunctionalization such as isocyanurate bonds, biuret bonds, and allophanate bonds, etc.,
[0160] The isocyanate crosslinking agent can be used alone or in combination of two or more. The amount of the isocyanate crosslinking agent is, for example, 0.01 mass part or more, 0.02 mass part or more, 0.05 mass part or more, or 0.1 mass part or more relative to 100 mass parts of (meth) acrylic polymer, and is less than 10 mass parts, less than 9 mass parts, less than 8 mass parts, less than 7 mass parts, less than 6 mass parts, or less than 5 mass parts, preferably more than 0.01 mass part and less than 10 mass parts, more than 0.02 mass part and less than 9 mass parts, more than 0.05 mass part and less than 8 mass parts. The amount can be appropriately adjusted in consideration of the prevention of peeling in the cohesion test and durability test.
[0161] It should be noted that an isocyanate crosslinking agent may not be used in the aqueous dispersion of the modified (meth)acrylic polymer prepared by emulsion polymerization, but a blocked isocyanate crosslinking agent may be used if necessary to facilitate reaction with water.
[0162] Epoxy crosslinking agents are polyfunctional epoxy compounds having two or more epoxy groups in one molecule. Examples of epoxy crosslinking agents include bisphenol A, epichlorohydrin type epoxy resins, ethylene glycol glycidyl ether, N,N,N′,N′-tetraglycidyl meta-xylene diamine, diglycidyl aniline, diamine glycidyl amine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, and sorbitan. Sugar alcohol polyglycidyl ether, glycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, glycerol diglycidyl ether, glycerol triglycidyl ether, polyglycerol polyglycidyl ether, sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, adipic acid diglycidyl ester, phthalic acid diglycidyl ester, triglycidyl-tris(2-hydroxyethyl)isocyanurate, resorcinol diglycidyl ether, bisphenol-S-diglycidyl ether, and epoxy resins having two or more epoxy groups in the molecule can also be mentioned. As the epoxy crosslinking agent, for example, the product made by Mitsubishi Gas Chemical Co., Ltd., trade name "TETRAD C", "TETRAD X" and the like can be used.
[0163] One epoxy crosslinking agent can be used alone, or two or more epoxy crosslinking agents can be used in combination. The amount of epoxy crosslinking agent used relative to 100 parts by mass of the (meth) acrylic polymer is, for example, 0.01 parts by mass or more, 0.02 parts by mass or more, 0.05 parts by mass or more, or 0.1 parts by mass or more, and 10 parts by mass or less, 9 parts by mass or less, 8 parts by mass or less, 7 parts by mass or less, 6 parts by mass or less, or 5 parts by mass or less, preferably 0.01 parts by mass or more and 10 parts by mass or less, 0.02 parts by mass or more and 9 parts by mass or less, or 0.05 parts by mass or more and 8 parts by mass or less. The amount of epoxy crosslinking agent used can be appropriately adjusted by considering the prevention of peeling in the cohesive force and durability test.
[0164] As a peroxide crosslinking agent, any peroxide crosslinking agent can be used as long as it generates free radical active species by heating and crosslinks the base polymer of the adhesive. However, considering the operability and stability, it is preferred to use a peroxide with a 1-minute half-life temperature of 80°C to 160°C, and more preferably a peroxide with a 1-minute half-life temperature of 90°C to 140°C.
[0165] Examples of the peroxide include di(2-ethylhexyl) peroxydicarbonate (1-minute half-life temperature: 90.6° C.), di(4-tert-butylcyclohexyl) peroxydicarbonate (1-minute half-life temperature: 92.1° C.), di-sec-butyl peroxydicarbonate (1-minute half-life temperature: 92.4° C.), tert-butyl peroxyneodecanoate (1-minute half-life temperature: 103.5° C.), tert-hexyl peroxypivalate (1-minute half-life temperature: 109.1° C.), tert-butyl peroxypivalate (1-minute half-life temperature: 110.3° C.), dilauroyl peroxide (1-minute half-life temperature: 111.7° C.), and dilauroyl peroxide (1-minute half-life temperature: 113.3° C.). Half-life temperature: 1 minute (half-life temperature: 116.4°C), dioctanoyl peroxide (half-life temperature: 117.4°C), 1,1,3,3-tetramethylbutyl peroxide-2-ethylhexanoate (half-life temperature: 124.3°C), di(4-methylbenzoyl) peroxide (half-life temperature: 128.2°C), dibenzoyl peroxide (half-life temperature: 130.0°C), tert-butyl peroxyisobutyrate (half-life temperature: 136.1°C), 1,1-di(tert-hexylperoxy)cyclohexane (half-life temperature: 149.2°C), etc. Among them, di(4-tert-butylcyclohexyl) peroxydicarbonate (1 minute half-life temperature: 92.1°C), dilauroyl peroxide (1 minute half-life temperature: 116.4°C), dibenzoyl peroxide (1 minute half-life temperature: 130.0°C), etc. are preferably used because of their particularly excellent cross-linking reaction efficiency.
[0166] It should be noted that the half-life of peroxide is an index representing the decomposition rate of peroxide, refers to the time until the residual amount of peroxide reaches half. About the half-life time under the decomposition temperature, arbitrary temperature in order to obtain the half-life at any time, in the manufacturer's catalogue etc., record to some extent, for example, be recorded in " Organic Peroxide Catalogue the 9th edition (May, 2003) " etc. of NOF Corporation.
[0167] The peroxide may be used alone or in combination of two or more. The amount of the peroxide is 0.02 to 2 parts by mass, preferably 0.05 to 1 part by mass, relative to 100 parts by mass of the (meth)acrylic polymer. The amount of the peroxide may be adjusted appropriately within this range to adjust processability, reprocessability, crosslinking stability, peelability, etc.
[0168] The amount of decomposed peroxide remaining after the reaction treatment can be measured by, for example, HPLC (high performance liquid chromatography).
[0169] More specifically, for example, about 0.2 g of the binder after the reaction treatment can be taken out each time, immersed in 10 ml of ethyl acetate, and extracted by shaking at 120 rpm for 3 hours at 25° C. using a shaker, and then left to stand at room temperature for 3 days. Next, 10 ml of acetonitrile is added, and the mixture is shaken at 120 rpm for 30 minutes at 25° C., and filtered using a membrane filter (0.45 μm) to obtain an extract, and about 10 μl of the obtained extract is injected into HPLC and analyzed, thereby obtaining the amount of peroxide after the reaction treatment.
[0170] In addition, as a crosslinking agent, an organic crosslinking agent and a polyfunctional metal chelate can be used in combination. A polyfunctional metal chelate is a chelate in which a polyvalent metal forms a covalent bond or a coordinate bond with an organic compound. As polyvalent metal atoms, Al, Cr, Zr, Co, Cu, Fe, Ni, V, Zn, In, Ca, Mg, Mn, Y, Ce, Sr, Ba, Mo, La, Sn, Ti, etc. can be cited. As atoms in organic compounds that form covalent bonds or coordinate bonds, oxygen atoms can be cited, and as organic compounds, alkyl esters, alcohol compounds, carboxylic acid compounds, ether compounds, and ketone compounds can be cited.
[0171] The amount of the active energy ray curable resin is, for example, 3 parts by mass or more and 60 parts by mass or less relative to 100 parts by mass of the (meth) acrylic polymer. The weight average molecular weight (Mw) before curing is 4000 or more and 50000 or less. As the active energy ray curable resin, for example, acrylate, epoxy, urethane, or thiol / ene ultraviolet curable resin can be appropriately used.
[0172] As the active energy ray-curable resin, a monomer and / or oligomer that is radically polymerized or cationically polymerized by active energy rays is used.
[0173] Examples of monomers that are radically polymerized by active energy rays include monomers having an unsaturated double bond such as a (meth)acryloyl group and a vinyl group. In particular, monomers having a (meth)acryloyl group are preferably used because of their excellent reactivity.
[0174] Specific examples of the monomer having a (meth)acryloyl group include allyl (meth)acrylate, caprolactone (meth)acrylate, cyclohexyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, heptadecafluorodecyl (meth)acrylate, glycidyl (meth)acrylate, caprolactone-modified 2-hydroxyethyl (meth)acrylate, isobornyl (meth)acrylate, morpholinyl (meth)acrylate, benzyl (meth)acrylate, ethyl acrylate, tripropylene glycol di(meth)acrylate, bisphenol A diglycidyl ether di(meth)acrylate, hydroxy neopentyl glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolpropane ethoxy tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, caprolactone-modified dipentaerythritol hexa(meth)acrylate, and the like.
[0175] As oligomers that undergo free radical polymerization by active energy rays, polyester (meth)acrylates, epoxy (meth)acrylates, urethane (meth)acrylates, etc., which are obtained by adding two or more unsaturated double bonds such as (meth)acryloyl groups and vinyl groups to the backbone of polyester, epoxy, urethane, etc. as the same functional groups as the monomers, can be used.
[0176] Polyester (meth)acrylate is obtained by reacting (meth)acrylic acid with a hydroxyl-terminated polyester obtained from a polyol and a polycarboxylic acid, and specific examples thereof include Aronix M-6000, 7000, 8000, and 9000 series manufactured by Toagosei Co., Ltd.
[0177] Epoxy (meth)acrylate is obtained by reacting (meth)acrylic acid with an epoxy resin, and specific examples thereof include Lipoxy SP and VR series manufactured by Showa Highpolymer Co., Ltd. and epoxy ester series manufactured by Kyoeisha Chemical Co., Ltd.
[0178] Urethane (meth)acrylate is obtained by reacting a polyol, an isocyanate, and a hydroxy (meth)acrylate, and specific examples thereof include ArtResin UN series manufactured by Negami Industries, NK Oligo U series manufactured by Shin-Nakamura Chemical Co., Ltd., and Ultraviolet UV series manufactured by Mitsubishi Chemical Corporation.
[0179] The photopolymerization initiator has a function of being excited and activated by ultraviolet ray irradiation to generate free radicals, and curing the polyfunctional oligomer through free radical polymerization. For example, acetophenone-based photopolymerization initiators such as 4-phenoxydichloroacetophenone, 4-tert-butyldichloroacetophenone, diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenylpropane-1-one, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropane-1-one, 1-(4-dodecylphenyl)-2-hydroxy-2-methylpropane-1-one, 4-(2-hydroxyethoxy)phenyl(2-hydroxy-2-propyl)ketone, 1-hydroxycyclohexylphenylketone, and 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropane-1-one; benzoin-based photopolymerization initiators such as benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, and 2,2-dimethoxy-2-phenylacetophenone; benzophenone, benzoylbenzoic acid, and benzylbenzoic acid; Benzophenone-based photopolymerization initiators such as methyl formylbenzoate, 4-phenylbenzophenone, hydroxybenzophenone, 4-benzoyl-4'-methyldiphenyl sulfide, and 3,3'-dimethyl-4-methoxybenzophenone; thioxanthone-based photopolymerization initiators such as thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-dichlorothioxanthone, 2,4-diethylthioxanthone, and 2,4-diisopropylthioxanthone; α-acyl oxime esters, acylphosphine oxides, methyl benzoylformate, benzil, camphorquinone, dibenzosuberone, 2-ethylanthraquinone, and 4',4"-diethylisophthalophenone; and special photopolymerization initiators. In addition, allylsulfonium hexafluorophosphate, sulfonium hexafluorophosphate, and bis(alkylphenyl)iodonium hexafluorophosphate can also be used as the photopolymerization initiator. Photocationic polymerization initiators such as salts.
[0180] The above-mentioned photopolymerization initiator may also be used in combination of two or more. Relative to 100 parts by mass of the above-mentioned active energy ray curable resin, the polymerization initiator is usually preferably mixed in a range of 0.5 parts by mass or more and 30 parts by mass or less, and more preferably in a range of 1 part by mass or more and 20 parts by mass or less. When it is less than 0.5 parts by mass, polymerization cannot be fully carried out, and the curing speed slows down. When it exceeds 30 parts by mass, the hardness of the cured sheet is sometimes reduced.
[0181] The active energy ray is not particularly limited, but is preferably ultraviolet light, visible light, and electron beam. The crosslinking treatment based on ultraviolet irradiation can be carried out using an appropriate ultraviolet source such as a high-pressure mercury lamp, a low-pressure mercury lamp, an excimer laser, a metal halide lamp, an LED lamp, etc. At this time, the irradiation amount of ultraviolet light can be appropriately selected according to the required crosslinking degree. Generally speaking, in the case of ultraviolet light, it is desired to be 0.2 J / cm 2 Above and 10J / cm 2The temperature during irradiation is not particularly limited, but is preferably about 140° C. in consideration of the heat resistance of the support.
[0182] When the adhesive contains a polyester polymer instead of a (meth)acrylic polymer, or contains a polyester polymer together with a (meth)acrylic polymer, for example, a polyester polymer having the following characteristics is preferable.
[0183] Type of carboxylic acid component (or characteristics of the skeleton, etc.): at least a dicarboxylic acid containing two carboxyl groups, specifically a dicarboxylic acid. The above-mentioned dicarboxylic acid is not particularly limited, and examples thereof include dimer acids derived from sebacic acid, oleic acid, and erucic acid. Other examples include glutaric acid, suberic acid, adipic acid, azelaic acid, 1,4-cyclohexanedicarboxylic acid, 4-methyl-1,2-cyclohexanedicarboxylic acid, dodecenylsuccinic anhydride, fumaric acid, succinic acid, dodecanedioic acid, hexahydrophthalic anhydride, tetrahydrophthalic anhydride, maleic acid, maleic anhydride, itaconic acid, citraconic acid, and other aliphatic or alicyclic dicarboxylic acids, terephthalic acid, isophthalic acid, phthalic acid, 1,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 4,4'-diphenyl dicarboxylic acid, 2,2'-diphenyl dicarboxylic acid, and 4,4'-diphenyl ether dicarboxylic acid. In addition to the above-mentioned dicarboxylic acids, tricarboxylic acids containing three or more carboxyl groups may also be used.
[0184] Types of diol components (or characteristics of the skeleton, etc.): diols containing at least two hydroxyl groups in the molecule, specifically diols. Dimer diols derived from fatty acid esters, oleic acid, erucic acid, etc., glycerol monostearate, etc. Other examples include aliphatic diols such as ethylene glycol and 1,2-propylene glycol. As diols other than aliphatic diols, ethylene oxide adducts and propylene oxide adducts of bisphenol A, ethylene oxide adducts and propylene oxide adducts of hydrogenated bisphenol A, etc.
[0185] As a crosslinking agent for introducing a crosslinked structure into a polyester polymer, an isocyanate crosslinking agent, Oxazoline crosslinking agents, aziridine crosslinking agents, silane crosslinking agents, alkyl ether melamine crosslinking agents, metal chelate crosslinking agents. The amount of the crosslinking agent is, for example, 2.0 parts by mass or more and 10.0 parts by mass or less relative to 100 parts by mass of the polyester polymer.
[0186] Next, refer to Figures 4 to 6The optical laminate 100B and 101B of another embodiment of the present invention are described. It should be noted that, for components having substantially the same functions as those in the above embodiment, the description of the above embodiment applies unless otherwise specified. The optical laminate 100B functions as a light distribution control element described in Patent Document 2 and can be manufactured using a roll-to-roll method. For reference, the disclosure of Patent Document 2 is incorporated herein in its entirety.
[0187] Figure 4 It is a schematic cross-sectional view of the optical layered bodies 100B and 101B, and shows a state in which the first optical sheet 10b is bonded to the surface 38s of the second optical sheet 30 via the adhesive layer 20b. Figure 5 It is a schematic perspective view of the optical sheet 10b included in the optical layered body 100B. Figure 6 It is a schematic cross-sectional view of a lighting device 200 including an optical layered body 102B and a light source 60 , and schematically shows the trajectory of light rays.
[0188] Reference Figure 4 and Figure 5 The optical laminate 100B has a first optical sheet 10b and an adhesive layer 20b, wherein the first optical sheet 10b has a first principal surface 12s having a concavo-convex structure and a second principal surface 18s on the opposite side to the first principal surface 12s, and the adhesive layer 20b is disposed on the first principal surface 12s side of the first optical sheet 10b. The optical laminate 101B has an optical laminate 100B and a second optical sheet 30 disposed on the adhesive layer 20a on the opposite side to the first optical sheet 10b. The concavo-convex structure of the first principal surface 12s of the optical sheet 10b includes a plurality of concave portions 14, and the surface of the adhesive layer 20b and the first principal surface 12s of the optical sheet 10b define a plurality of spaces 14 (indicated by the same reference symbols as the concave portions) in the plurality of concave portions 14. The adhesive layer 20 b is an essential component for defining the space 14 of the optical layered body 100B, and is a part of the optical layered body 100B.
[0189] The concavo-convex structure of the optical sheet 10b includes a flat portion 10s in contact with the adhesive layer 20b. The concavo-convex structure includes, for example, a plurality of convex portions 15 having a trapezoidal cross section. The concavo-convex structure has a flat portion 10s in contact with the adhesive layer 20b. Therefore, the concavo-convex structure of the optical sheet 10b is similar to the concavo-convex structure of the optical sheet 10b. Figure 1 Compared with the concavo-convex structure of the prism surface of the prism sheet 10a shown, the adhesive layer 20b is less likely to invade the concave portion. Therefore, by using the above adhesive, an optical laminate 100B can be obtained in which the adhesive layer 20b does not invade the plurality of spaces 14 and is less likely to change over time.
[0190] The optical sheet 10b can be made of the same material and by the same method as the known prism sheet or microlens sheet. The size and shape of the concavo-convex structure of the optical sheet 10b can be appropriately changed (Patent Document 2). However, as described above, the optical sheet 10b is different from the known prism sheet or microlens sheet in that it functions as an optical laminate 100B that defines the space 14 only by bonding with the adhesive layer 20.
[0191] like Figure 4 As shown, in the optical laminate 101B, the second optical sheet 30 is configured in a manner that the surface 22s of the adhesive layer 20b is bonded to its surface 38s. The material constituting the second optical sheet 30 can adopt any appropriate material according to the purpose. As the material of the second optical sheet 30, for example, a light-transmitting thermoplastic resin can be cited, and more specifically, for example, a film formed by (meth) acrylic resins such as polymethyl methacrylate (PMMA) and polycarbonate (PC) resins can be cited.
[0192] The space 14 of the optical laminate 100B is defined by the surface 16s and the surface 17s as a part of the first principal surface 12s of the first optical sheet 10b, and the surface 28s of the adhesive layer 20b. Shown here is an example in which the surface 16s is inclined (more than 0° and less than 90°) relative to the sheet surface (horizontal direction of the figure), and the surface 17s is substantially perpendicular to the sheet surface, but it is not limited to this, and various changes can be made (refer to patent document 2).
[0193] The optical laminate 100B is, for example, Figure 6 As shown, it is used in a lighting device 200. A light guide plate 50 is provided on the side of the adhesive layer 20b of the optical stack 100B opposite to the first optical sheet 10b. The optical stack 100B and the light guide plate 50 are collectively referred to as an optical stack 102B. The optical stack 102B is bonded to the light guide plate 50 at the surface 22s of the adhesive layer 20b of the optical stack 100B. The optical stack 102B is configured in such a way that light from a light source (e.g., an LED) 60 is incident on the light receiving surface of the light guide plate 50, and the light introduced into the light guide plate 50 is as follows. Figure 6 As indicated by arrows in the figure, total reflection (TIR) occurs at the interface 16s and the interface 14s formed by the space 14. The light that has been totally reflected at the interface 14s (the surface 28s of the adhesive layer 20b) is guided within the light guide plate 50 and the adhesive layer 20b, and the light that has been totally reflected at the inclined surface 16s is emitted from the surface 18s of the optical laminate 100B to the outside. By adjusting the shape, size, configuration density, etc. of the space 14, the distribution (light distribution) of the light emitted from the optical laminate 100B can be adjusted. Here, the refractive indexes of the light guide plate 50, the adhesive layer 20b, and the optical sheet 10b are preferably equal.
[0194] exist Figures 4 to 6 , the cross-sectional shape of the convex portion 15 is a trapezoidal example, but the shape of the convex portion 15 is not limited to the example shown in the figure, and various changes can be made. By adjusting the shape and size of the convex portion 15, the shape, size, and arrangement density of the space 14 can be adjusted. For example, an example of a laminate having a plurality of spaces inside is described in International Publication No. 2011 / 124765. For reference, the disclosure of International Publication No. 2011 / 124765 is incorporated in its entirety in this specification.
[0195] Hereinafter, experimental examples (Examples and Comparative Examples) will be described.
[0196] [Example 1]
[0197] (Preparation of Adhesive Composition Solution)
[0198] First, an acrylic polymer was prepared. In a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, and a condenser, 62.9 parts by mass of n-butyl acrylate (BA), 33.9 parts by mass of 4-acryloylmorpholine (ACMO), 2.9 parts by mass of acrylic acid (AA), 0.3 parts by mass of 4-hydroxybutyl acrylate (4HBA), and 0.1 parts by mass of 2,2'-azobisisobutyronitrile as a polymerization initiator were added to the flask together with ethyl acetate in such a way that the total amount of monomers became 50% by mass, and nitrogen was introduced while slowly stirring. After nitrogen replacement for 1 hour, the liquid temperature in the flask was maintained at about 58°C, and a polymerization reaction was performed for 8 hours to obtain an acrylic polymer. Here, after 2 hours from the start of the polymerization reaction, ethyl acetate was added dropwise in a manner that the solid content reached 35% by mass over 3 hours. That is, an acrylic polymer solution having a solid content of 35% by mass of the acrylic polymer was obtained.
[0199] Next, the obtained acrylic polymer solution was mixed with 7 parts by mass of an ultraviolet curable urethane acrylate resin A (weight average molecular weight Mw: 5500) in terms of solid content, 0.7 parts by mass of 2,2-dimethoxy-1,2-diphenylethane-1-one (trade name "Omnirad651", manufactured by IGM JAPAN Corporation) as a photopolymerization initiator, and 0.1 parts by mass of 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane (trade name "TETRAD-C", manufactured by Mitsubishi Gas Chemical Co., Ltd.) as a crosslinking agent to prepare an adhesive composition solution.
[0200] (Adhesive Sheet Production)
[0201] An adhesive composition solution was applied to one side of a 38 μm thick polyethylene terephthalate (PET) film (trade name "MRF38", manufactured by Mitsubishi Chemical Corporation) after silicone release treatment to form an adhesive composition solution layer. At this time, the thickness of the adhesive composition solution layer was applied in such a way that the thickness after drying (i.e., the thickness of the adhesive composition layer) reached 1 μm. The adhesive composition solution layer was dried at 150°C for 3 minutes to remove the solvent of the adhesive composition solution layer, and the acrylic polymer was cross-linked using a cross-linking agent to obtain an adhesive composition layer having a first cross-linked structure. Next, an adhesive composition layer was attached to the release-treated surface of a 38 μm thick polyethylene terephthalate (PET) film (trade name "MRE38", manufactured by Mitsubishi Chemical Corporation) after silicone release treatment to produce an adhesive sheet (first laminate) having a laminated structure of PET film / adhesive composition layer / PET film.
[0202] (Production of optical laminate)
[0203] A piece of the peeled PET film was peeled off from the obtained adhesive sheet (first laminate), and the exposed adhesive composition layer was bonded to an acrylic resin film (thickness: 20 μm). The other separator (PET film) was further peeled off and bonded to a laminate having a pitch P of 10 μm, a height H of 5.0 μm, and a vertex angle θ of 90° (see Figure 1 ) was prepared by mixing a prism surface of a concave-convex prism sheet (manufactured by Japan Special Optical Resins Co., Ltd., model "LPV90-0.01S") to obtain a laminate (the second laminate) having a laminate structure of acrylic resin film / adhesive composition layer / prism sheet.
[0204] Next, the second laminate is irradiated with ultraviolet light from the upper surface (acrylic resin film side) of the second laminate to cure the ultraviolet curable resin in the adhesive composition layer, thereby forming an adhesive layer having a second crosslinking structure in addition to the first crosslinking structure, thereby obtaining an optical laminate (third laminate) of Example 1 having a laminated structure of acrylic resin film / adhesive layer / prism sheet (optical sheet). The optical laminate (third laminate) of Example 1 is as follows: Figure 2 The optical laminate 101A shown in the figure has a first optical sheet (prism sheet) 10a, an adhesive layer 20a, and a second optical sheet (acrylic resin film) 30. Ultraviolet irradiation was performed using an LED lamp (manufactured by Quark Technology Co., Ltd., peak illuminance: 200 mW / cm 2 、Accumulated light quantity 1500mJ / cm 2(wavelength: 345 to 365 nm)), and the illuminance of ultraviolet rays was measured using a UV Power Puck (manufactured by FusionUV Systems JAPAN Co., Ltd.).
[0205] [Example 2]
[0206] (Preparation of Adhesive Composition Solution)
[0207] In Example 2, the following aspects are different from Example 1: In the preparation of the acrylic polymer, n-butyl acrylate, 4-acryloylmorpholine, acrylic acid, and 4-hydroxybutyl acrylate are set to 67.8 mass parts / 29.0 mass parts / 2.9 mass parts / 0.3 mass parts, respectively. In the obtained acrylic polymer solution, 0.1 mass parts of 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane (trade name "TETRAD-C", manufactured by Mitsubishi Gas Chemical Co., Ltd.) as a crosslinking agent is added to prepare an adhesive composition solution with respect to 100 mass parts of the solid content of the polymer. That is, the adhesive composition solution of Example 2 does not contain a UV curable resin and a photopolymerization initiator.
[0208] (Adhesive Sheet Production)
[0209] An adhesive composition solution was applied to one side of a 38 μm thick polyethylene terephthalate (PET) film (trade name "MRF38", manufactured by Mitsubishi Chemical Corporation) after silicone release treatment to form an adhesive composition solution layer. At this time, the adhesive composition solution layer was applied in such a way that the thickness after drying (i.e., the thickness of the adhesive layer) reached 1 μm. The adhesive composition solution layer was dried at 150° C. for 3 minutes to remove the solvent of the adhesive composition solution layer, and the acrylic polymer was cross-linked using a cross-linking agent, thereby obtaining an adhesive layer having a cross-linked structure.
[0210] In the above-mentioned Example 1, the adhesive composition solution contains an acrylic polymer, a crosslinking agent, an ultraviolet curable resin, a photopolymerization initiator, and a solvent. In Example 1, the adhesive composition solution layer formed by the adhesive composition solution is dried at 150°C for 3 minutes, and the acrylic polymer is crosslinked by the crosslinking agent, thereby forming an adhesive composition layer having a first crosslinked structure, and then the ultraviolet curable resin of the adhesive composition layer is cured, thereby forming an adhesive layer having a second crosslinked structure in addition to the first crosslinked structure. In contrast, in Example 2, the adhesive composition solution does not contain an ultraviolet curable resin and a photopolymerization initiator. In Example 2, the adhesive composition solution layer formed by the adhesive composition solution is dried at 150°C for 3 minutes, and the acrylic polymer is crosslinked by the crosslinking agent, thereby forming an adhesive layer having a crosslinked structure.
[0211] Next, an adhesive layer was attached to the release-treated surface of a 38 μm thick polyethylene terephthalate (PET) film (trade name "MRE38", manufactured by Mitsubishi Chemical Corporation) that had been subjected to silicone release treatment to produce an adhesive sheet (first laminate) having a laminate structure of PET film / adhesive layer / PET film.
[0212] (Production of optical laminate)
[0213] A piece of PET film that had been subjected to peeling treatment was peeled off from the obtained adhesive sheet (first laminate), and the exposed adhesive layer was bonded to an acrylic resin film (thickness: 20 μm), and the other separator (PET film) was further peeled off and bonded to a prism surface of a prism sheet (manufactured by Japan Special Optical Resins Co., Ltd., model "LPV90-0.01S") having a pitch of 10 μm and a height of 5.0 μm, thereby obtaining an optical laminate of Example 2 (second laminate). The optical laminate of Example 2 is as follows. Figure 2 The optical layered body 101A shown includes a first optical sheet (prism sheet) 10 a , an adhesive layer 20 a , and a second optical sheet (acrylic resin film) 30 .
[0214] [Example 3]
[0215] (Preparation of Adhesive Composition Solution)
[0216] In Example 3, in the preparation of an acrylic polymer, 95.0 parts by mass of n-butyl acrylate, 5.0 parts by mass of acrylic acid, and 0.2 parts by mass of 2,2'-azobisisobutyronitrile as a polymerization initiator were added to a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, and a condenser so that the total amount of monomers was 40.0% by mass, together with ethyl acetate, and nitrogen was introduced while slowly stirring. After nitrogen replacement for 1 hour, the liquid temperature in the flask was maintained at about 63°C, and a polymerization reaction was performed for 6 hours. Then, ethyl acetate was added so that the solid content was 40% by mass, and an acrylic polymer was obtained. In the obtained acrylic polymer solution, 6.0 parts by mass of 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane (trade name "TETRAD-C", manufactured by Mitsubishi Gas Chemical Co., Ltd.) as a crosslinking agent was added to 100 parts by mass of the solid content of the polymer to prepare an adhesive composition solution.
[0217] (Adhesive Sheet Production)
[0218] The same procedure as in Example 2 was carried out.
[0219] (Production of optical laminate)
[0220] The same procedure as in Example 2 was carried out.
[0221] [Example 4]
[0222] (Preparation of Adhesive Composition Solution)
[0223] First, a polyester polymer was prepared. A three-necked separable flask was equipped with a stirrer, a thermometer, and a vacuum pump, and 48.9 g of dimer acid (trade name "Pripol 1009", molecular weight 567, manufactured by Croda Japan Co., Ltd.), 51.1 g of dimer alcohol (trade name "Pripol 2033", molecular weight 537, manufactured by Croda Japan Co., Ltd.), and 0.1 g of dibutyltin oxide (manufactured by Kanto Chemical Co., Ltd.) as a catalyst were added thereto, and the temperature was raised to 200° C. while stirring in a reduced pressure atmosphere (2.0 kPa or less), and the temperature was maintained. The reaction was continued for about 5 hours to obtain a polyester polymer.
[0224] The obtained polyester polymer solution was mixed with 4.0 parts by mass of isocyanurate of hexamethylene diisocyanate (trade name "Coronate HX", manufactured by Tosoh Corporation) as a crosslinking agent based on 100 parts by mass of the polymer solid content to prepare an adhesive composition solution.
[0225] (Adhesive Sheet Production)
[0226] An adhesive composition solution was applied to one side of a 38 μm thick polyethylene terephthalate (PET) film (trade name "MRF38", manufactured by Mitsubishi Chemical Corporation) after silicone release treatment to form an adhesive composition solution layer. At this time, the thickness of the adhesive composition solution layer was applied so that the thickness after drying (i.e., the thickness of the adhesive layer) reached 3 μm. The adhesive composition solution layer was obtained by drying the adhesive composition solution layer at 120°C for 3 minutes to remove the solvent. Next, the adhesive composition layer was attached to the release-treated surface of a 38 μm thick polyethylene terephthalate (PET) film (trade name "MRE38", manufactured by Mitsubishi Chemical Corporation) after silicone release treatment, and placed at 40°C for 3 days to produce an adhesive sheet (first laminate) having a laminated structure of PET film / adhesive layer / PET film. By treating at 40° C. for 3 days, the polyester polymer in the adhesive composition layer was crosslinked by the crosslinking agent to obtain an adhesive layer having a crosslinked structure. In the step of drying at 120° C. for 3 minutes, a crosslinking reaction may partially occur.
[0227] (Production of optical laminate)
[0228] The same procedure as in Example 2 was carried out.
[0229] [Example 5]
[0230] (Preparation of Adhesive Composition Solution)
[0231] In Example 5, the following aspects are different from Example 1: in the preparation of the acrylic polymer, n-butyl acrylate, 4-acryloylmorpholine, acrylic acid, and 4-hydroxybutyl acrylate are set to 74.6 mass parts / 18.6 mass parts / 6.5 mass parts / 0.3 mass parts, respectively. In addition, the following aspects are different from Example 1: in the preparation of the adhesive composition solution, in the obtained acrylic polymer solution, 10 mass parts of ultraviolet curable urethane acrylate resin A as an ultraviolet curable resin is added in terms of solid content relative to 100 mass parts of the polymer, and 1.0 mass part of 4-(2-hydroxyethoxy)phenyl(2-hydroxy-2-propyl)ketone (trade name "Omnirad2959", manufactured by IGM JAPAN Contract Co., Ltd.) as a photopolymerization initiator and 0.6 mass part of 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane (trade name "TETRAD-C", manufactured by Mitsubishi Gas Chemical Co., Ltd.) as a crosslinking agent are added. The other steps were carried out in the same manner as in Example 1.
[0232] (Adhesive Sheet Production)
[0233] The same procedure as in Example 1 was carried out.
[0234] (Production of optical laminate)
[0235] The same procedure as in Example 1 was carried out.
[0236] [Example 5a]
[0237] An optical layered body of Example 5a having a laminated structure of acrylic resin film / adhesive layer / optical sheet (concave-convex shape-imparting film) was prepared in the same manner as in Example 5 except that the following concave-convex shape-imparting film 70 was used as the optical sheet.
[0238] (Manufacturing of Concavoconvex Shaped Film)
[0239] The concave-convex shaped film was manufactured according to the method described in the Japanese Patent Table 2013-524288 Gazette. Specifically, the surface of the polymethyl methacrylate (PMMA) film was coated with a varnish (Sanyo Chemical Industries, Ltd., Finecure RM-64), and an optical pattern was embossed on the film surface containing the varnish, and then the varnish was cured to manufacture the target concave-convex shaped film. The total thickness of the concave-convex shaped film was 130 μm, and the haze was 0.8%. A top view obtained by observing a part of the manufactured concave-convex shaped film 70 from the concave-convex surface side is shown in Fig. 7A In addition, Fig. 7A The 7B-7B' cross-sectional view of the concave-convex shaped film is shown in Figure 7B . A plurality of concave portions 74 with a triangular cross section having a length L of 80 μm, a width W of 14 μm, and a depth H of 10 μm are arranged at intervals of a width E (155 μm) in the X-axis direction. In addition, such a pattern of concave portions 74 is arranged at intervals of a width D (100 μm) in the Y-axis direction. The density of the concave portions 74 on the surface of the concave-convex shaped film is 3612 pieces / cm 2 . Figure 7B Both θa and θb in θ are 41°, and the area occupied by the recessed portion 74 when the film is viewed from the concave-convex surface side is 4.05%.
[0240] [Example 6]
[0241] Example 6 differs from Example 5 in that in the preparation of the adhesive sheet (first laminate), the thickness of the adhesive composition solution layer was set so that the thickness after drying (i.e., the thickness of the adhesive composition layer) was 5 μm.
[0242] [Example 6a]
[0243] An optical layered body of Example 6a having a laminated structure of acrylic resin film / adhesive layer / optical sheet (concave-convex shape-imparting film) was prepared in the same manner as in Example 6 except that the concave-convex shape-imparting film 70 was used as the optical sheet.
[0244] [Example 7]
[0245] Example 7 differs from Example 5 in that in the preparation of the adhesive sheet (first laminate), the thickness of the adhesive composition solution layer was set so that the thickness after drying (i.e., the thickness of the adhesive composition layer) was 10 μm.
[0246] [Example 7a]
[0247] An optical layered body of Example 7a having a laminated structure of acrylic resin film / adhesive layer / optical sheet (concave-convex shape-imparting film) was prepared in the same manner as in Example 7 except that the concave-convex shape-imparting film 70 was used as the optical sheet.
[0248] [Comparative Example 1]
[0249] Comparative Example 1 differs from Example 2 in that in the preparation of the acrylic polymer, n-butyl acrylate, 4-acryloylmorpholine, acrylic acid, and 4-hydroxybutyl acrylate are respectively 77.4 parts by mass / 19.4 parts by mass / 2.9 parts by mass / 0.3 parts by mass. The other steps are the same as in Example 2.
[0250] [Comparative Example 2]
[0251] Comparative Example 2 differs from Example 2 in that in the preparation of the acrylic polymer, n-butyl acrylate, 4-acryloylmorpholine, acrylic acid, and 4-hydroxybutyl acrylate are respectively 92.0 parts by mass / 4.8 parts by mass / 2.9 parts by mass / 0.3 parts by mass. The other steps are the same as in Example 2.
[0252] The optical layered bodies of Examples 1 to 7 and Comparative Examples 1 and 2 were evaluated as follows. Table 1 shows the evaluation results.
[0253] <Evaluation of creep deformation rate>
[0254] A laminate of adhesive layers (thickness 1 mm) was produced as follows.
[0255] Examples 1 and 5 to 7: The same operation as the above-mentioned adhesive sheet (the first laminate) was performed, but the thickness of the adhesive composition layer was set to 10 μm, and 4 adhesive sheets (the fifth laminate) having a laminated structure of PET film / adhesive composition layer (thickness 10 μm) / PET film were prepared with a size of 20 cm wide and 30 cm long. Then, ultraviolet rays were irradiated to the fifth laminate to cure the ultraviolet curable resin of the adhesive composition layer, thereby obtaining an adhesive sheet (the sixth laminate) having a laminated structure of PET film / adhesive layer (thickness 10 μm) / PET film. By repeatedly performing the steps of laminating the adhesive layers of the adhesive sheet (the sixth laminate) obtained by laminating the adhesive layers of the multilayers and dividing the laminate of the adhesive layer into a plurality of test pieces (cutting out a plurality of test pieces), a laminate (thickness 1 mm, size 4 cm×6 cm) having a total of 100 layers of adhesive layers (thickness 10 μm) was obtained. The ultraviolet irradiation on the fifth laminate was performed using an LED lamp (manufactured by Quark Technology Co., Ltd., peak illuminance: 200 mW / cm 2 、Accumulated light quantity 1500mJ / cm 2 (wavelength: 345 to 365 nm)), and the illuminance of ultraviolet rays was measured using a UV Power Puck (manufactured by Fusion UV Systems JAPAN Co., Ltd.).
[0256] Examples 2 to 4 and Comparative Examples 1 and 2: The same operation as the above-mentioned adhesive sheet (first laminate) was performed, but the thickness of the adhesive layer was set to 10 μm, and four adhesive sheets (the sixth laminate) having a laminated structure of PET film / adhesive layer (thickness 10 μm) / PET film were prepared with a size of 20 cm wide and 30 cm long. By repeatedly performing the steps of laminating the adhesive layers of the adhesive sheet (the sixth laminate) obtained by laminating the adhesive layers of the plurality of layers and dividing the laminated body of the adhesive layer into a plurality of test pieces (cutting out a plurality of test pieces), a laminated body (thickness 1 mm, size 4 cm×6 cm) having a total of 100 adhesive layers (thickness 10 μm) was obtained.
[0257] A cylinder with a diameter of 8 mm (height of 1 mm) was punched out from the laminate (thickness of 1 mm) of the adhesive layer obtained as described above to prepare a test piece. A viscoelasticity measuring device (device name "ARES G-2", manufactured by TA Instruments JAPAN Co., Ltd.) was used to apply a stress of 10,000 Pa to the test piece at a measuring temperature of 50°C for 30 minutes, and the deformation rate was measured after 1 second and 30 minutes.
[0258] In this specification, the "creep deformation rate" of the adhesive layer is set to the "creep deformation rate" obtained by the above method using a laminate (thickness 1mm) using an adhesive layer. According to the experiment of the present inventors, no significant difference was observed in the creep deformation rate of a laminate with a thickness of 1mm between a laminate formed by stacking 20 layers of adhesive layers with a thickness of 50μm, a laminate formed by stacking 100 layers of adhesive layers with a thickness of 10μm, and a laminate formed by stacking 200 layers of adhesive layers with a thickness of 5μm. That is, within the range where the thickness of each adhesive layer constituting the laminate is at least 5μm or more and 50μm or less, the creep deformation rate of a laminate with a thickness of 1mm does not depend on the thickness of the adhesive layer. According to the research of the present inventors, when the thickness of each adhesive layer is 0.1μm or more, the creep deformation rate of a laminate with a thickness of 1mm takes a substantially constant value.
[0259] <180° peel adhesion to polymethyl methacrylate (PMMA)>
[0260] For Examples 2 to 4 and Comparative Examples 1 and 2, a piece of PET film after the peeling treatment was peeled off from the obtained adhesive sheet (first laminate), and the surface of the exposed adhesive layer was bonded to a polyethylene terephthalate (PET) film with a thickness of 25 μm (trade name "Lumirror S-10", manufactured by Toray Industries, Ltd.) to obtain a test piece.
[0261] The test piece was cut into a width of 20 mm, and another PET film after peeling treatment was peeled off, and the surface of the exposed adhesive layer was bonded to a polymethyl methacrylate (PMMA) plate (thickness 2 mm, trade name "Acrylite", manufactured by Mitsubishi Chemical Corporation), and the adhesion (mN / 20 mm) relative to the PMMA plate was measured as a test piece. The pressure bonding when bonding with the PMMA plate was performed by reciprocating a 2 kg roller once, and after bonding for 30 minutes, the 180° peeling adhesion was measured using a tensile compression tester (device name "AGS-50NX", manufactured by Shimadzu Corporation) under the following conditions.
[0262] Peeling speed: 300mm / min
[0263] Measurement conditions: Temperature: 23±2℃, Humidity: 65±5%RH
[0264] For Examples 1 and 5 to 7, the adhesive sheet (first laminate) was used to prepare the test piece in the same manner as in Examples 2 to 4 and Comparative Examples 1 and 2, and after laminating with the PMMA plate (i.e., after obtaining a laminate of PET film (Lumirror S-10) / adhesive composition layer / PMMA plate), ultraviolet light was irradiated from the PET film side to prepare the test piece. The ultraviolet light irradiation was performed using an LED lamp (manufactured by Quark Technology Co., Ltd., peak illuminance: 200 mW / cm 2 、Accumulated light quantity 1500mJ / cm 2 (wavelength: 345 to 365 nm)), and the illuminance of ultraviolet rays was measured using a UV Power Puck (manufactured by Fusion UV Systems JAPAN Co., Ltd.).
[0265] <Evaluation of Haze>
[0266] A laminate of adhesive layers (thickness 80 μm) was produced as follows.
[0267] Examples 1 and 5 to 7: By the same method as in the above-mentioned <Evaluation of Creep Deformation Rate>, an adhesive sheet (6th laminate) having a laminated structure of PET film / adhesive layer (thickness 10 μm) / PET film was prepared with a size of 20 cm wide and 30 cm long. 8 test pieces were cut out from the obtained adhesive sheet (6th laminate), and 8 layers of adhesive layers (thickness 10 μm) were laminated to obtain a laminated body of adhesive layers (thickness 80 μm).
[0268] Examples 2 to 4 and Comparative Examples 1 and 2: By the same method as in the above-mentioned <Evaluation of Creep Deformation Rate>, an adhesive sheet (the sixth laminate) having a laminated structure of PET film / adhesive layer (thickness 10 μm) / PET film was prepared with a size of 20 cm in width and 30 cm in length. Eight test pieces were cut out from the obtained adhesive sheet (the sixth laminate), and eight layers of adhesive layers (thickness 10 μm) were laminated to obtain a laminated body of adhesive layers (thickness 80 μm).
[0269] By laminating a laminate of an adhesive layer (thickness 80 μm) with a PET film after a silicone release treatment, a laminate having a laminate structure of a PET film / adhesive layer (thickness 80 μm) / PET film was obtained. A piece of separator (PET film) was peeled off from the laminate having a laminate structure of a PET film / adhesive layer (thickness 80 μm) / PET film, and the laminate of the adhesive layer was laminated to a glass plate (trade name "EAGLE XG", manufactured by Corning, thickness 0.7 mm), and the other separator was further peeled off to prepare a test piece having a laminate structure of a laminate of an adhesive layer / glass plate. The haze of the test piece was measured using a haze meter (device name "HZ-1", manufactured by SUGA Testing Instrument Co., Ltd.) and D65 light.
[0270] In this specification, the "haze" of the adhesive layer is defined as the "haze" obtained by the above method for a laminate (80 μm thick) using the adhesive layer. The haze of a laminate with a thickness of 80 μm does not depend on the thickness of each adhesive layer constituting the laminate.
[0271] <Evaluation of diffuse transmittance>
[0272] The acrylic resin film of the optical laminate of each example or comparative example was placed on a haze meter (device name "HZ-1", manufactured by SUGA Test Instruments Co., Ltd.) with the light source side as the light source, and the diffuse transmittance was measured using D65 light. The diffuse transmittance just after lamination (within 5 minutes) (recorded as "diffuse transmittance (just after lamination)" in Table 1) and the diffuse transmittance 10 days after lamination (stored at temperature: 23±2°C, humidity: 65±5%RH) (recorded as "diffuse transmittance (after 10 days)" in Table 1) were measured. The obtained diffuse transmittance was determined according to the following criteria.
[0273] Diffuse transmittance just after bonding (within 5 minutes)
[0274] ◎:More than 96%
[0275] ○: 95% or more and less than 96%
[0276] △: 94% or more and less than 95%
[0277] ×: Less than 94%
[0278] Diffusion transmittance 10 days after bonding
[0279] ◎:More than 90%
[0280] ○: 85% or more and less than 90%
[0281] △: 84% or more and less than 85%
[0282] ×: less than 84%
[0283] [Table 1]
[0284]
[0285] The optical laminates of Examples 1 to 7 all satisfy the following requirements: the diffuse transmittance immediately after lamination (within 5 minutes) is 95% or more, and the diffuse transmittance 10 days after lamination is 85% or more. In contrast, the diffuse transmittance of the optical laminates of Comparative Examples 1 and 2 is less than 95% immediately after lamination (within 5 minutes), and the diffuse transmittance 10 days after lamination is less than 85%. Based on these results, it can be considered that for the adhesive layers of Examples 1 to 7, when the adhesive layers are laminated to the optical sheet, the penetration of the adhesive layers into the recessed portions of the optical sheet and the change over time in the degree of penetration of the adhesive layers into the recessed portions are suppressed.
[0286] Regarding the optical laminates of Examples 5a, 6a and 7a using a concave-convex imparting film having a plurality of concave portions on the surface as an optical sheet, 10 days after the optical sheet and the adhesive composition layer were bonded together, the cross-sections (including the concave-convex imparting film 70) of the optical laminates of Examples 5a, 6a and 7a were examined by an optical microscope (ECLIPSE LV100 manufactured by Nikon Solutions Co., Ltd.) at a magnification of 1500 times. Figure 7B For Examples 5a, 6a, and 7a, it was confirmed based on the observed images that the adhesive layer did not substantially penetrate into the concave portion 74 of the concave-convex shaping film 70, and that the time-dependent change in the degree of penetration of the adhesive layer into the concave portion was suppressed.
[0287] The adhesive layers of the optical laminates of Examples 1 to 7 all satisfy the following conditions: the creep deformation rate (creep deformation rate A) after 1 second is 10% or less, and the creep deformation rate (creep deformation rate B) after 30 minutes is 16% or less. In contrast, the creep deformation rate A of the adhesive layers of the optical laminates of Comparative Examples 1 and 2 exceeds 10% or the creep deformation rate B exceeds 16%. It can be considered that there is a certain correlation between the creep deformation rate of the adhesive layer and the diffuse transmittance of the optical laminate. According to the results of Examples 1 to 7, from the perspective of suppressing the invasion of the adhesive layer into the concave portion of the optical sheet when the adhesive layer is bonded to the optical sheet and the time-dependent change in the degree of the invasion of the adhesive layer into the concave portion, it is preferred that the creep deformation rate (creep deformation rate A) after 1 second is 10% or less, and the creep deformation rate (creep deformation rate B) after 30 minutes is 16% or less.
[0288] Example 2 and Comparative Examples 1 and 2 differ only in the mass ratio of n-butyl acrylate (BA) to 4-acryloylmorpholine (ACMO) when preparing the (meth)acrylic polymer. In Example 2, BA:ACMO=70:30, in Comparative Example 1, BA:ACMO=80:20, and in Comparative Example 2, BA:ACMO=95:5. The ratio of the component derived from ACMO to the whole adhesive is 29.0% by mass in Example 2, 19.4% by mass in Comparative Example 1, and 4.8% by mass in Comparative Example 2. However, the present invention is not limited to this example. For example, as can be seen from Example 3, a (meth)acrylic polymer can be prepared without using a nitrogen-containing (meth)acrylic monomer. The adhesives of Examples 1 and 5 to 7 contain a cured product of an ultraviolet curable resin in addition to the component derived from the nitrogen-containing (meth)acrylic monomer having a nitrogen-containing cyclic structure (Example 1: 31.4% by mass relative to the whole adhesive, Examples 5 to 7: 16.7% by mass relative to the whole adhesive). In the case of a cured product further containing an ultraviolet curable resin, the preferred ratio of the nitrogen-containing (meth)acrylic monomer having a nitrogen-containing ring structure may change. In addition, it is known that an adhesive containing a polyester polymer may be used instead of a (meth)acrylic polymer as in Example 4.
[0289] Industrial Applicability
[0290] The optical layered body of the present invention can be widely used in optical devices such as display devices and lighting devices.
Claims
1. An optical laminate, comprising: A first optical sheet having a first main surface having a concavo-convex structure and a second main surface opposite to the first main surface; and an adhesive layer disposed on the first main surface side of the first optical sheet, The concavo-convex structure includes a plurality of concave portions, and the surface of the adhesive layer and the first main surface of the first optical sheet define a plurality of spaces in the plurality of concave portions. The concavo-convex structure includes a flat portion in contact with the adhesive layer, The adhesive layer has a creep deformation rate of 10% or less when a stress of 10,000 Pa is applied at 50° C. for 1 second, and a creep deformation rate of 16% or less when a stress of 10,000 Pa is applied at 50° C. for 30 minutes in a creep test using a rotational rheometer. The 180° peeling adhesion of the adhesive layer to the PMMA film is 10 mN / 20 mm or more. The adhesive layer comprises at least one of the following polymers (1) and (2), (1) a (meth)acrylic polymer, which is a copolymer of a nitrogen-containing (meth)acrylic monomer and at least one other monomer, wherein the nitrogen-containing (meth)acrylic monomer has a nitrogen-containing cyclic structure; (2) Polyester polymers.
2. The optical layered body according to claim 1, wherein: The adhesive layer has a haze of 0.01% or more and 5% or less.
3. The optical layered body according to claim 1 or 2, wherein: The adhesive layer has a thickness of 0.1 μm or more and 20 μm or less. 4 . The optical layered body according to claim 1 , further comprising a copolymer of a carboxyl group-containing acrylic monomer and at least one other monomer (except the nitrogen-containing (meth)acrylic monomer).
5. The optical layered body according to claim 1 or 2, wherein: The adhesive layer contains a polyester polymer.
6. The optical layered body according to claim 1 or 2, wherein: The adhesive layer contains the (meth)acrylic polymer.
7. The optical layered body according to claim 6, wherein: The (meth)acrylic polymer is cross-linked.
8. The optical layered body according to claim 6, wherein: The adhesive layer does not contain a grafted polymer.
9. The optical layered body according to claim 6, wherein: The adhesive layer further includes a cured product of an active energy ray-curable resin.
10. The optical layered body according to claim 9, wherein: The adhesive layer is formed by curing the active energy ray-curable resin of the adhesive composition layer including the (meth)acrylic polymer, the active energy ray-curable resin, and a polymerization initiator.
11. A laminate comprising: The adhesive layer of the optical laminate according to any one of claims 1 to 9, and a substrate having a main surface subjected to a release treatment, The release-treated main surface of the substrate is bonded to the adhesive layer.
12. A laminate comprising: The adhesive composition layer constituting the adhesive layer of the optical laminate according to claim 10, and A substrate having a main surface subjected to a release treatment, The release-treated main surface of the substrate and the adhesive composition layer are bonded together.
13. A method for producing the optical layered body according to any one of claims 1 to 10, the method comprising: A step of bonding the first optical sheet and the adhesive layer together.
14. The manufacturing method according to claim 13, wherein: The process is carried out by a roll-to-roll method. 15 . The optical layered body according to claim 1 , further comprising a second optical sheet, wherein the second optical sheet is disposed on the side of the adhesive layer opposite to the first optical sheet side. 16 . The optical layered body according to claim 10 , further comprising a second optical sheet, wherein the second optical sheet is disposed on the side of the adhesive layer opposite to the first optical sheet side.
17. A production method, which is a production method of the optical layered body according to claim 15 or 16, comprising any one of step A1 and step A2, The step A1 is to bond a first laminate to the second optical sheet, wherein the first laminate is formed by laminating the first optical sheet and the adhesive layer. The step A2 is to bond a second laminate to the first optical sheet, wherein the second laminate is formed by laminating the adhesive layer and the second optical sheet.
18. The manufacturing method according to claim 17, wherein: The method includes the step A1, and the step A1 includes a step of bonding the first laminate and the second optical sheet by a roll-to-roll method; or, This method includes the step A2, and the step A2 includes a step of bonding the second laminate and the first optical sheet by a roll-to-roll method. 19 . An optical device comprising the optical layered body according to claim 1 .
20. A method for producing the optical layered body according to claim 10, the method comprising: Step A, providing the adhesive composition layer on the first main surface of the first optical sheet; and In step B, in a state where the adhesive composition layer is provided on the first main surface of the first optical sheet, the active energy ray-curable resin of the adhesive composition layer is cured.
21. The manufacturing method according to claim 20, wherein: The step A includes a step of bonding the first optical sheet and the adhesive composition layer together by a roll-to-roll method.
22. A manufacturing method, which is a manufacturing method of the optical layered body according to claim 16, the method comprising: Either step A1 or step A2, and In step B after step A1 or step A2, The step A1 is to bond a first laminate to the second optical sheet, wherein the first laminate is formed by laminating the first optical sheet and the adhesive composition layer. The step A2 is to bond a second laminate to the first optical sheet, wherein the second laminate is formed by laminating the adhesive composition layer and the second optical sheet. The step B cures the active energy ray-curable resin contained in the adhesive composition layer.
23. The manufacturing method according to claim 22, wherein: The method includes the step A1, and the step A1 includes a step of bonding the first laminate and the second optical sheet by a roll-to-roll method; or, This method includes the step A2, and the step A2 includes a step of bonding the second laminate and the first optical sheet by a roll-to-roll method.
Citation Information
Patent Citations
Method and apparatus for culturing animal cell
JP1981058490A
Optical laminated sheet, method of manufacturing optical laminated sheet, light source with optical laminated sheet, and image display device with optical laminated sheet
JP2012007046A
Internal cavity optical element
JP2013524288A
Laminate structure with embedded cavities and related method of manufacture
WO2011124765A1
Light distribution structure and element, related method and uses
WO2019087118A1